Calcium Oxide Derived from Okpella Limestone as a Heterogeneous Catalyst for Biodiesel Production: Synthesis, Characterisation and Stability Assessment - Abdulrahman S. USMAN; Folorunsho ABERUAGBA; Moses A. OLUTOYE; Umar MUSA; Mohammed ALHASSAN (FUDMA Journal of Engineering and Technology, 2025)
Sustainable energy alternatives have increased the pace of the research on low-cost and low-environmental-impact catalysts used in the production of biodiesel. This paper examines the synthesis, characterisation, and performance of calcium oxide (CaO) catalysts produced from Okpella limestone, which is in Edo State, Nigeria. This was done by calcining the limestone at 900°C over a period of five hours to break down the calcium carbonate (CaCO₃) into catalytically active CaO. FTIR, XRD, XRF, SEM, BET, and TGA methods were used to characterise the raw and the calcined materials to assess their physicochemical characteristics and their appropriateness to the production of biodiesel. The XRD and the FTIR analyses verified the conversion of calcite into phase-pure CaO with high crystallinity. XRF and EDS data revealed that it contained 89.23 wt.% of CaO, which signified high purity and high basicity. SEM micrographs showed a porous irregular morphology, and BET analysis showed mesoporosity with a high surface area of 61.21 m²/g, a pore diameter of 3.14 nm and a pore volume of 0.11 cm³/g, which are significant characteristics for efficient transesterification. Complete decomposition of CaCO₃ at 650°C to 800°C was confirmed by thermogravimetric analysis. Catalytic stability was shown to be six reaction cycles, with reusability tests showing biodiesel yields of over 90% before deactivation occurred gradually due to surface fouling and leaching. These results make Okpella limestone a viable, low-cost, and locally available raw material in the manufacture of high-grade CaO catalysts. The research advocates the production of cleaner biodiesels, and it helps Nigeria shift into renewable energy systems.